Pentingnya Media Sosial Dalam pemasaran Usaha Kita Madu di Binjai - Pratiwi Putri Lestari; Sukmawati Sukmawati; Dedi S. Simajuntak; Putri Rizky; Rika Silvany (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Kita Madu business in Binjai is a business that sells pure honey. This activity process aims to help Kita Madu's business in increasing honey sales. Honey sales are carried out not only by selling directly, but also using online sales, namely social media. By utilizing existing social media, you can promote and see consumer enthusiasm for the products being sold. In promoting products, business owners can create their own advertisements by making videos about how to consume honey and providing articles about the benefits of honey for the body. Sales using social media can assess customer satisfaction with testimonials sent by consumers. Based on the results of observations in a month using social media, sales of Kita Madu have increased, because we also have a large number of followers on social media, making it easier to promote Kita Madu.